HUMORAL IMMUNITY TO THE DAMAGE OF LIPID METABOLISM IN PATIENTS WITH RENOCARDIAC SYNDROME - Demikhova, N. V. (Ukrainian Journal of Nephrology and Dialysis, 2017)
A total of 289 patients with chronic renocardiac syndrome, 204 of them with chronic glomerulonephritis and 85 diabetic nephropathy. The worsening of the lipid metabolism, depending on the degree of chronic renal failure (CRF), I noted in the degree of CKD, manifested increased low density lipoprotein (LDL) of 1.22 times (p=0.004), triglycerides (p=0.02), atherogenicity index (p<0.0001) and decreased high-density lipoprotein (HDL) cholesterol (p<0.001). The coefficient of LDL / HDL ratio was greatest in patients with CRF I, which indicates the most intense pro-atherogenic processes in these patients. The biological role of education lipoprotein immune complexes (LPIC) is confirmed by us revealed a statistically significant negative correlation between the ratio and the atherogenic LDL IgG (r=- 0,3; p=0.04), and LDL atherogenic factor IgM (r=-0,46, p=0.01) in patients with chronic renal failure group 1. A statistically significant negative correlation between daily proteinuria and LDL IgG, LDL IgM (r=-0,3; p=0,005; r=-0,4; p=0.004, respectively), which suggests the assumption of our damaging effect LPIC on the renal glomerulus.